Congenital rubella with agenesis of the inferior cerebellar vermis and total anomalous pulmonary venous drainage. (26th June 2013) - Cluver, C.; Meyer, R.; Odendaal, H.; Geerts, L.
ABSTRACT Congenital rubella infection has been associated with a number of abnormalities including cardiac, central nervous system and placental complications. We present a case with multiple fetal abnormalities detected on prenatal ultrasound, and confirmed postnatally, that included a single umbilical artery, severe tricuspid regurgitation, micrognathia and agenesis of the inferior cerebellar vermis. Postnatal echocardiography additionally revealed unobstructed total anomalous pulmonary venous drainage (TAPVD) into the coronary sinus. Placental examination showed signs of placentitis, and polymerase chain reaction on neonatal serum was positive for rubella. Following a multidisciplinary team review, it was decided to provide only supportive care, and the infant died at 6 months of age owing to a respiratory tract infection. To our knowledge, TAPVD and agenesis of the inferior cerebellar vermis have not been reported previously in association with congenital rubella infection. This case illustrates how congenital infection may present in atypical ways and stresses the importance of considering congenital infection in the differential diagnosis of fetal anomalies when multiple features are present. Copyright © 2013 ISUOG. Published by John Wiley & Sons Ltd.